Evidence of introgressive hybridization between the morphologically divergent land snails Ainohelix and Ezohelix. (12th February 2015) - Morii, Yuta; Yokoyama, Jun; Kawata, Masakado; Davison, Angus; Chiba, Satoshi
<x xml:space="preserve">Abstract</x> Hybridization between different taxa is likely to take place when adaptive morphological differences evolve more rapidly than reproductive isolation. When studying the phylogenetic relationship between two land snails of different nominal genera, Ainohelix editha and Ezohelix gainesi, from Hokkaido, Japan, using nuclear internal transcribed spacer and mitochondrial 16S ribosomal DNA, we found a marked incongruence in the topology between nuclear and mitochondrial phylogenies. Furthermore, no clear association was found between shell morphology (which defines the taxonomy) and nuclear or mitochondrial trees and morphology of reproductive system. These patterns are most likely explained by historical introgressive hybridization between A. editha and E. gainesi. Because the shell morphologies of the two species are quite distinct, even when they coexist, the implication is that natural selection is able to maintain (or has recreated) distinct morphologies in the face of gene flow. Future studies may be able to reveal the regions of the genome that maintain the morphological differences between these species. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, 115, 77–95.